Prevalence of cystic echinococcosis in Iran: a systematic review and meta-analysis. Issue 3 (7th June 2017) - Khalkhali, H.R.; Foroutan, M.; Khademvatan, S.; Majidiani, H.; Aryamand, S.; Khezri, P.; Aminpour, A.
Abstract: As a significant zoonosis, cystic echinococcosis (CE) is endemic in some parts of the world, such as the Middle East. There are studies on the prevalence of this infection in animal and human reservoirs in Iran; hence, we conducted this meta-analysis to elucidate the prevalence of CE in Iran. English (PubMed, Scopus, Web of Science, Science Direct and Google Scholar) and Persian (Magiran, Iran Medex, Iran Doc and SID) databases were explored. In the case of definitive, animal and human intermediate hosts, 37, 90 and 33 studies, respectively, have been included in the current review from January 1990 to December 2015. According to outcomes of the heterogeneity test, either Der Simonian and Laird's random-effects method or Mantel–Haenszel's fixed-effects method were employed to pool the estimations. The pooled prevalence of Echinococcus granulosus infection in definitive hosts was calculated as 23.6% (95% confidence interval (CI) = 17.6–30.1%). The weighted prevalence of animal and human hydatidosis was calculated as 15.6% (95% CI = 14.2–17.1%) and 4.2% (95% CI = 3.0–5.5%), respectively. Meanwhile, most cases of human hydatidosis were in southern Iran, with a prevalence of 5.8% (3.2–9.2%). In terms of human hydatidosis, more infections were found in rural regions, and mostly in female individuals. Egger's regression test revealed publication bias, with a remarkable impact on total prevalence of the infection in animal intermediate hosts ( P < 0.001), while it was not significant in human hosts ( P = 0.4) and definitive hosts ( P = 0.3). According to the weighted estimated prevalence of cystic echinococcosis and its financial burden, implementing appropriate control programmes should be compulsory to decrease the burden of the disease in Iran.